WEAR ANALYSIS TOOL CARBIDE INSERTS DUE TO DRY MACHINING STAINLESS STEEL - Chendri Johan*, O. Sutresman, A.Y. Aminy (International Journal of Research Science and Management, 2017)
Turning is a machining process that aims to shape the material in particular cylindrical. In turning there are a number of problems that arise and may interfere with the process of production, one of which is a tool wear. This research examines the hardness and wear of tools by using tool Al2O3 + TiO2 and tool TiO2. Experimental method is the method used in this study where rockwell hardness testing use testing and measurement of edge wear toolmaker microscope using a measuring instrument. Stainless steel is the material used in the machining process. Hardness testing results obtained to tool Al2O3 + TiO2 is 87,82 HRC and tool TiO2 is 87,52 HRC. Measurement of the average flank wear tools Al2O3 + TiO2 is 0,040 VB and tools TiO2 is 0,016 VB. Cutting speed significant effect on tool wear on turning the results of stainless steel grade 301, depth of cut and feed rate had no significant effect. But simultaneously, all three of these parameters significantly affect tool wear.